Thes easonable duration of proceedings and the moral damage resulting from the delay in of requests for social security benefits (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The demand for speed within the scope of the Public Administration, which manifests itself in current discussions through the slowness with which the state apparatus serves the citizen, must be understood as a re-reading of access to the Public Administration, in the broad conception of due process of law - either in view of the express provision of article 5, LXXVIII, of the Federal Constitution, or as a reflection of the efficiency stamped on the caput of article 37 of the Major Text. Indeed, it is imperative to point out that the late delivery of the good of life sought and guaranteed to the interested party, who knocks on the doors of the Public Power, mischaracterizes security and the constitutional commitment to citizens, the foundation of the Democratic Rule of Law. This is not to disregard the bilateral failure in the formation of Brazilian citizenship, which is undeniably clumsy both in the fulfillment of duties and in the reception of fundamental rights. The subject of this text, however, is the non-proportional delay in the provision of public services by the social security agency, the National Social Security Institute (INSS). It assesses whether such a delay can constitute damage to the personality and, consequently, characterize a hypothesis of compensation for moral damage. The investigation is timely, especially in the current context in which successive targets and deadlines have been set for the judgment of lawsuits by the Judiciary, since the establishment of the National Council of Justice. There is an undoubted connection between speed in the delivery of administrative services and speed in the provision of justice, because, as has already been consolidated in the procedural field, the magistrate's task does not end with the resolution of the dispute in the cognition phase, but presupposes, with greater importance, the effective realization of the decision in the world of facts.This materialization, in turn, is linked to the good or bad performance of the administrative bodies.In other words - and addressing the specific issue under discussion - it should be noted that if the INSS does not decide on the administrative request in the time expected or does not comply with the court decision within the period set by the judge, there will be a greater volume of requests from the parties to the Judiciary.What is recognized as a difficulty is the abstract setting of a reasonable time limit for the solution of the specific case in the administrative sphere.Indeed, there is no escaping the open discussion of reasonableness and proportionality, in other words: the still raging debate about the scope of principles and the determination of undetermined legal concepts.
Keywords: social security benefit; delay in assessment; reasonable duration of proceedings; moral damage